Link between Periodontal Disease and Coronary Artery Disease: Bangladesh Perspective - Islam, AKMM; Rahman, MM; Ullah, M; Yeasmin, L (Cardiovascular Journal, 2014)
Coronary artery disease (CAD) is an increasingly important medical and public healthproblem, and is the leading cause of mortality in Bangladesh. Besides conventional risk factors and ethnicity, a number of emerging risk factors may explain the undue prevalence of CAD in this population. Periodontal disease (PD) is one of them, with prevalence of approximately 50%. As with many other diseases, PD is associated with CAD, and the association is independent of conventional risk factors. Low socioeconomic condition, illiteracy and ignorance, metabolic syndrome, nutritional deficiencies including hypovitaminosis D presumably contribute to the prevalence of PD in Bangladesh. In fact, PD and CAD share some cardiometabolic risk factors including diabetes mellitus, obesity and metabolic syndrome. Future research will hopefully explore different aspects of both public health problems, namely, PD and CAD in the country. The information gathered thereby, will help formulate policy to promote good oral health and tackle the deadly epidemic of CAD more efficiently. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20800 Cardiovasc. j. 2014; 7(1): 44-54